Digital Marketing Strategy in Promoting the City's Brand - Kadar Nurjaman (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
This project intends to build a digital marketing plan to promote a city brand containing a marketing manual or guide and an elaboration of the digital system for mobile and online apps. This research is based on city branding in the city of Samarinda, East Kalimantan Province, which aims in addition to increase the selling value of tourism and business but also to be an attraction in seizing potential resources so that, in turn, it is expected to be able to drive the development of the city itself. The technique is qualitative; organized and semi-structured interviews and direct observation of visitors. Consequently, digital marketing guidelines and digital apps are produced, which represent simply one click to access the world without limits and boost cities' competitiveness.